Lifestyle and Dietary Risk Factors Associated with Renal Stones in Duhok City - Saleem Ali, Niwar; Hussein Kadhim, Miaad (Journal of Neonatal Surgery, 2025)
Background: Renal stones also called nephrolithiasis or urolithiasis, is a medical issue involves the formation and sometimes the passage of crystalline within the urinary tract. The aim of present study to assess the lifestyle and dietary factors associated with renal stones in Duhok City. Methods: A cross-sectional design was conducted, data were collected during period from September 1, 2024, to December 31, 2024. A convenience sample of patients with renal stones who were admitted to the Urology Ward and visited the Urology Consultation Unit at Azadi Teaching Hospital was chosen for inclusion in the present study. Results: The present study revealed a total of 260 participants. The age distribution indicated a predominance of younger individuals, with 59.23% falling within the 18 to 44 years age group. The highest number of participants were males (156; 60%). The majority of participants (98.08%) walked for 1–74 minutes daily, while only 18.08% in moderate physical activities and 26.92% in vigorous activities. Additionally, most participants consumed calcium (25.48%), sodium (25.48%), and sugar (23.46%), 1–3 times per week, respectively. Conclusions: Several lifestyle factors and various dietary habits that play the crucial role for renal stone formation. Also, regular exercise, adequate drinking water, and less consuming of sodium, calcium, sugar that help to prevent stone formation.